Cyclic voltammetry electrodeposition and modification of silver nanoparticles-reduced graphene oxide electrode for immunosensing - Jamil, Asilah (2015)
A silver nanoparticles (AgNPs) and reduced graphene oxide (rGO) nanocomposite electrodeposited on an indium tin oxide (ITO) glass slide using cyclic voltammetry (CV) technique is reported. The modified ITO was used as a platform for the development of a new electrochemical hydrogen peroxide (H2O2) biosensor, in which horseradish peroxidase (HRP) tagged antibody acted as a recognition element. The AgNPs-rGO nanocomposite was synthesized via CV electrodeposition technique in a three-electrode electrochemical cell. Silver-ammonia solution [Ag(NH3)2OH] was used as a precursor of silver and was prepared by adding ammonia to a silver nitrate (AgNO3) solution until complete absence of precipitate was achieved. The [Ag(NH3)2OH] solution was mixed with GO and CV was performed to allow electrodeposition to take place. By applying a negative potential, the GO nanosheets with the absorbed [Ag(NH3)2]+ ions were electrodeposited on ITO, simultaneously reducing GO to rGO nanosheets and [Ag(NH3)2]+ ions to AgNPs, forming a brown and uniform AgNPs-rGO nanocomposite thin film. CV and chronoamperometry (CA) techniques were employed in the determination of electrode responses and applicability. The AgNPS-rGO/ITO modified electrode outperformed the bare electrode remarkably, in which the surface area calculated was 0.36 cm2 compared to bare ITO, which was 0.27 cm2. The electrochemical conductivity were enhanced significantly by 40-fold, resulting in a notable amplified electrical signal for the detection of H2O2. The limit of detection was calculated as 120 μM at the signal-to-noise ratio of 3 with a linear range from 25 μM to 500 μM (R2 = 0.9944) through CV, while using CA, this modified electrode exhibited a wider linear range from 25 μM to 1355 μM (R2 = 0.9992) with the detection limit estimated as 10 μM at the signal-to-noise ratio of 3. Meanwhile, the immunoassay was prepared by immobilizing carcinoembryonic antigen (CEA) between the primary antibody and detection antibody, which was HRP-labelled tagged antibody. The sandwich-type immunoassay represented the sandwich enzymelinked immunosorbent assay (ELISA) method that is commonly used as a diagnostic tool for cancer detection. The amperometric response of the biosensor was based on the electrocatalytic reduction of H2O2 by HRP due its ability to catalyze H2O2 reduction process at a lower potential via direct electron transfer. Thus, it was used to enhance response signal and boost analytical sensitivity of the immunoassay. The CV analysis using the sandwich-type immunoassay configuration resulted in a linear range of 25 μM - 500 μM for the detection of H2O2, with a detection limit of 214 μM. Meanwhile, CA offered a wider linear range of 25 μM - 1450 μM, with a detection limit 5.3 μM. Therefore, it had been proven that the current-time response provided a more sensitive measurement towards the detection of H2O2. The resulting biosensor also exhibited excellent stability with a relative standard deviation of 5.0% (n = 3) and remarkable reproducibility of only a 10% decrease in the peak current upon observation after 10 days. The biosensor was also highly selective towards H2O2 when compared against various interferences.